African Potato (Hypoxis Spp): Diversity and Comparison of the Phytochemical Profiles and Cytotoxicity Evaluation of four Zimbabwean Species - C. Zimudzi (Journal of Applied Pharmaceutical Science, 2014)
The Hypoxis corm has a catalogue of medicinal uses and also serves as a source of food. Most scientific research on Hypoxis has centred on Hypoxis hemerocallidea although many other species are exploited medicinally. Hypoxis corms look similar and this has resulted in different species being prescribed and sold as the same species raising important public health issues of the efficacy and quality of the medicines sold. The aim of this study was to investigate and compare the phytochemical profiles and cytotoxicity of Hypoxis hemerocallidea, Hypoxis rigidula, Hypoxis galpinii and Hypoxis obtusa. Corm methanolic extracts of the four species were qualitatively screened for different phytochemicals following standard methods. Tests indicated presence of terpenoids, saponins, cardiac glycosides, tannins and reducing sugars and negative for alkaloids, flavonoids and anthraquinones in the four Hypoxis species. Cytotoxic effects of the plants were assessed through Brine shrimp lethality (BSL) bioassay. LC50 values ranged from 6.3 -409 mg/ml showing that the plants are non toxic.
Keywords: Hypoxis hemerocallidea, Hypoxis rigidula, Hypoxis galpinii and Hypoxis obtusa.